Determination of Consumption Decisions, Wealth, Individual Data, Political Economy and Theory - Dr. James E. Curtis, Jr. (Modern Perspectives in Economics, Business and Management Vol. 9, 2021)
James Curtis Jr presents decision-making considerations of “individuals” in an economy with grouped individuals, owners of firms, and social planner(s), conditional on wealth constraints with applied social economic considerations.